(untitled) (Progressive Agriculture, 2019)
Paddy in Bangladesh is an important cereal crop for national food security. Harvesting is the process of collecting mature paddy from the field. Timely harvesting operation is known as crucial and influential processes on quantity, quality and production cost of paddy. The aim of the study was to assess the manual and mechanical harvesting systems of paddy in southern delta region of Bangladesh in terms of labor cost, infield harvesting losses, and time required for harvesting. Several experiments were conducted to compare mechanical and manual harvesting systems. Mechanical harvesting of Aman paddy (November-December 2016) and Boro paddy (April-May 2017) was conducted using two models of reaper and a mini-combine harvester at Dumuria and Wazirpur Upazilas of Khulna and Barisal districts, respectively. An experiment was also conducted at the same locations to determine labor requirement and time for harvesting paddy manually. To determine manual harvesting loss, an experiment was conducted at BAU farm, Mymensingh. Total cost savings in paddy harvesting were found 52% and 37% for mini-combine harvester and reaper, respectively over manual harvesting system. Similarly, labor savings using mini-combine harvester and reaper were found 65% and 52%, respectively over manual harvesting system. The total harvesting losses (including harvesting, threshing and cleaning) were also found 1.24%, 4.22% and 6.36% for using mini-combine, reaper and manual harvesting systems, respectively. The results indicated that manual harvesting is a slow and cost involving system. On the other hand, lack of awareness among farmers about the benefits of mechanical harvesting system and lack of skill manpower for operating and servicing harvesters are major barriers for adopting mechanized harvesting system in southern delta region. This study revealed that mechanical harvesting of paddy using either reaper or mini-combine harvester will assist to strengthen food security in southern delta of Bangladesh. Progressive Agriculture, Vol. 30, Suppl. 1: 57-64, 2019